Air Cannula Vs. Weckcel Sponge in Manipulation of Corneal Flap and Incidence of SPK (Superficial Punctate Keratitis) after LASIK - Vipul Bhandari; Jagadeesh K. Reddy; Vineet Joshi (The Ophthalmology, 2015)
Aim: To compare the difference in early post-operative Superficial Punctate Keratopathy (SPK) in patients by using either blunt cannula or Weck-cel sponge intra-operatively to handle the corneal flap during Laser-assisted in situ keratomileusis (LASIK). Materials and Methods: A randomized prospective comparative study comprising of 192 eyes of 96 patients undergoing LASIK in both eyes were selected for this study. Two groups were made. First group included 96 eyes using air cannula (group 1) and the second included 96 eyes using a Weck-cel sponge (group 2) to manipulate the corneal flap intra-operatively. Both the groups were later compared for different grades of SPKs. Results: Out of total 192 eyes 51(26.8%) eyes showed Grade 4 SPKs of which 49(96%) belonged to the Weck-cel sponge group and 2(4%) eyes belonged to the air canula group. Conclusion: In this study we found that group 2 associated with m